High‐risk behaviours, and their associations with mental health, adherence to antiretroviral therapy and HIV parameters, in HIV‐positive men who have sex with men. Issue 2 (12th December 2018) - Pool, ERM; Winston, A; Bagkeris, E; Vera, JH; Mallon, PWG; Sachikonye, M; Post, FA; Pozniak, A; Boffito, M; Anderson, J; Williams, I; Johnson, M; et al.
Abstract : Objectives: To investigate the patterns and frequency of multiple risk behaviours (alcohol, drugs, smoking, higher risk sexual activity) among men who have sex with men (MSM) living with HIV. Methods: Cross sectional study. Results: 147 out of 819 HIV‐positive MSM exhibited a high‐risk phenotype (defined as >3 of smoking, excess alcohol, sexually transmitted infection and recent recreational drug use). This phenotype was associated with younger age, depressive symptoms and <90% adherence in multivariable logistic regression. Conclusion: In a cohort of MSM, a small, but significant proportion exhibited multiple concurrent risk behaviours.